استخدام مقياسي عدم التأكد (UC)و Lambdaفي دراسة العلاقة بين مكان إقامة الأسرة السورية وتوفر خدمات المسكن الأساسية "دراسة تطبيقية مقارِنة بين ريف وحضر المحافظات السورية " - روماني هدى (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتضمن هذا البحث دراسة التأثير المتبادل بين مكان إقامة الأسرة في الريف أو الحضر وتوفر الخدمات الأساسية للأسرة الممثلة بكل من مصدر الكهرباء، وسيلة الصرف الصحي، مصدر المياه المستخدم للشرب و وجود خط الهاتف الأرضي أو الهاتف الخلوي، باستخدام مقياسي Lambda و Uncertainty Coefficient (UC) ، وقد شملت عينة البحث 14040 أسرة تمثل إجمالي سكان القطر وتوزعهم حسب المحافظات وعلى مستوى الريف والحضر. صنفت هذه الأسر في جداول تقاطعية وفق متغيرين: أحدهما الخدمات الأساسية وله حالتان (توفر جميع الخدمات) و(عدم توفر جميع الخدمات)، والآخر مكان إقامة الأسرة وله حالتان (الريف) و(الحضر) وذلك من أجل كل محافظة من محافظات سورية. اختُبرتْ فرضيتا العدم المتعلقتان بكل من مقياس Lambdaومقياس UC اللتان أثبتتا معنوية العلاقة بين مكان إقامة الأسرة في الريف أو الحضر وتوفر الخدمات الأساسية لها في مختلف المحافظات غير أن هذه العلاقة اختلفت شدتها من محافظة لأخرى، مما يعطي مؤشراً حول آلية التنمية الواجب اتباعها بحسب خصوصية كل محافظة. This research studies the mutual influence between the residence of households in rural or urban areas, and providing basic housing services to these households represented by each of the following: electricity supply, means of sanitation, water sources used for drinking, and the availability of phones or cell phones by using Lambda and Uncertainty Coefficient (UC) measures. The study is based on a sample of 14,040 households representing Syria’s population, and their distribution across provinces and rural and urban areas. These households are classified in cross tables according to two variables: the first one is the basic services which have two cases: availability of all services and lack of all services. The second one is the residence of each household which has two cases: rural and urban. This pattern is applied for each province in Syria. The tested Null Hypotheses concerning Lambda measure and UC measure have been rejected, which demonstrates significant relationship between place of residence of households in rural or urban areas and providing basic housing services in the various governorates, but this relationship have various intensities across provinces, which gives an indication of the mechanism of development that must be followed according to the nature of each province.